Analysis of congenital hypomyelinating Egr2(Lo/Lo) nerves identifies Sox2 as an inhibitor of Schwann cell differentiation and myelination - Le, Nam (National Academy of Sciences, 2005)
Egr2 is a transcription factor required for peripheral nerve myelination in rodents, and mutations in Egr2 are associated with congenital hypomyelinating neuropathy (CHN) in humans. To further study its role in myelination, we generated mice harboring a hypomorphic Egr2 allele (Egr2(Lo)) that survive for up to 3 weeks postnatally, a period of active myelination in rodents. These Egr2(Lo/Lo) mice provided the opportunity to study the molecular effects of Egr2 deficiency on Schwann cell biology, an analysis that was not possible previously, because of the perinatal lethality of Egr2-null mice. Egr2(Lo/Lo) mice phenocopy CHN, as evidenced by the severe hypomyelination and increased numbers of proliferating Schwann cells of the peripheral nerves. Comparison of sciatic nerve gene expression profiles during development and after crush injury with those of Egr2(Lo/Lo) Schwann cells revealed that they are developmentally arrested, with down-regulation of myelination-related genes and up-regulation of genes associated with immature and promyelinating Schwann cells. One of the abnormally elevated genes in Egr2(Lo/Lo) Schwann cells, Sox2, encodes a transcription factor that is crucial for maintenance of neural stem cell pluripotency. Wild-type Schwann cells infected with Sox2 adenovirus or lentivirus inhibited expression of myelination-associated genes (e.g., myelin protein zero; Mpz), and failed to myelinate axons in vitro, but had an enhanced proliferative response to β-neuregulin. The characterization of a mouse model of CHN has provided insight into Schwann cell differentiation and allowed the identification of Sox2 as a negative regulator of myelination.